1997
DOI: 10.1007/s003300050261
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of posterior pituitary for evaluation of the neurohypophyseal function in idiopathic and autosomal dominant neurohypophyseal diabetes insipidus

Abstract: We investigated the role of MR imaging for evaluation of the functional status of the neurohypophyseal system in both idiopathic central diabetes insipidus (DI) and familial autosomal dominant neurohypophyseal DI. The patients and family with DI were analyzed retrospectively for the presence or absence of posterior pituitary gland hyperintense signal on MR images. A total of 19 adult patients with idiopathic central DI, 7 members of a family with autosomal dominant DI and 20 control subjects were included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Consistent with the results of Rutishauser et al [8] and others [25,26,27], all 3 investigated patients of the two families did not show the ‘bright spot’ in T 1 -weighted pituitary images. Signal intensity is discussed to correlate closely with posterior lobe function as it is suspected to result from neurovesicles in axon endings of AVP-producing neurons [8, 28].…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with the results of Rutishauser et al [8] and others [25,26,27], all 3 investigated patients of the two families did not show the ‘bright spot’ in T 1 -weighted pituitary images. Signal intensity is discussed to correlate closely with posterior lobe function as it is suspected to result from neurovesicles in axon endings of AVP-producing neurons [8, 28].…”
Section: Discussionsupporting
confidence: 81%
“…The signal returned from the posterior pituitary gland by T1-weighted MRI is related to its functional integrity [1] and loss of the normal posterior pituitary bright spot (PPS) is described in primary diabetes insipidus [2,3] and in water intoxication [4]; however, this absence of PPS has not yet been reported in children with TBM but occurs frequently in our clinical experience and may be related to the serum sodium and SIADH levels in these patients.…”
Section: Introductionmentioning
confidence: 85%
“…The signal can change (loss of the bright spot) in conditions where there is no ADH production, such as primary diabetes insipidus [2,3]. A transient reduction in posterior pituitary bright signal has also been described in a child with water intoxication [4].…”
Section: Mr Appearance Of the Pituitary Gland In Childrenmentioning
confidence: 95%
“…The accumulation of this preprohormone might account for the persistentposterior pituitary bright spot and for the variable appearance of MRI scans of members of the same family [40, 43, 44]. It has been suggested that these patients are able to store small amounts of AVP, but cannot release it normally [45]. …”
Section: Posterior Pituitary Deficiencymentioning
confidence: 99%